THE POPULATION OF WHITE-BELLIED PLANTHOPPERS AND THEIR NATURAL ENEMIES: THE NEW PEST OF CORN IN LAMPUNG - Swibawa, I Gede; Susilo, Franciscus Xaverius; Hariri, Agus Muhammad; ., Solikhin (Universitas Lampung, 2018)
The Population of White-Bellied Planthoppers and their Natural Enemies: the New Pest of Corn in Lampung. The white-bellied planthoppers (Stenocranus pasificus), hereinafter referred to as WBP, as new exotic pests in Lampung have the poten-tial to reduce corn production and threaten national food sovereignty. Therefore, population of the pest needs to be managed to prevent the outbreaks. However, there is still limited information on the bio-ecology of WBP. Thus, this research was conducted to: 1) study the population growth pattern of WBP on various corn cultivars and 2) document the natural enemies of WBP. This research was carried out from May to December 2017with a survey method on several corn fields in South Lampung and planting trial on an experimental field of Faculty of Agriculture, Universitas Lampung planted with 3 corn cultivars, i.e. Madura, P-27 and NK which were arranged in randomized complete block design with three replications. The results of the research showed: 1) there were two peaks of population density observed during plant growth. The peak of adult stage of macroptera population density occurred at 17 and 53 days after planting (dap), the highest number of leaves with oviposition mass was observed at 24 and 65 dap, while the peak of population density of nymph stage and adult stage of brachiptera occurred at 31 and 75 dap; 2) Natural enemies of WBP included 9 orders, classified as specialist predators of mirid bugs (Cyrtorhynus) and rove beetles (Paederus), and generalist predators of spiders (Araneae) and lady beetles (Coccinellidae). The population of specialist predators was fluctuated depending on WBP population, while the population of generalist predators was varied.